Preformed Silos versus Traditional Abdominal Wall Closure in Gastroschisis: 163 Infants at a Single Institution - Charlesworth, Paul; Akinnola, Ibiyinka; Hammerton, Charlotte; Praveena, Pranithia; Desai, Ashish; Patel, Shailish; Davenport, Mark (European Journal of Pediatric Surgery, 2014)
Introduction The surgical management of gastroschisis (GS) is controversial. The most commonly used strategy for abdominal wall closure is surgery on day 1 of life with the aim of primary closure (PC) or construction of a surgical silo (SS) and secondary closure thereafter. The other widely used technique is application of a preformed silo (PFS) and reduction of contents over a few days before final closure. There is still a paucity of comparative outcome data.Methods A retrospective case note review of all infants initially treated at a single institution between October 1993 and October 2012. PFS was adopted as the technique of choice in April 2005. Infants with closed or closing GS were excluded. Data are presented as median (range). p < 0.05 were significant.Results There were 163 infants (156 complete data sets). PFSs were applied in 67 infants and PC/SS were applied in 89 infants of whom 19 infants required a SS. There was no statistical difference between gestational age (p = 0.8), birth weight (p = 0.7), time to first (p = 0.07) and full enteral feeding (p = 0.08), length of hospital stay (p = 0.17), or necrotizing enterocolitis (p = 0.4) and mortality (p = 0.4). Infants treated with PC + SS were closed on day 0 (range, 0–11 days) versus day 6 (range, 2–22 days) of life (p < 0.001). PC + SS were ventilated for day 5 (range, 1–22 days) versus day 3.5 (range, 0–20 days) days (p = 0.01).Conclusion Infants treated with PFS required less ventilation than those treated by PC + SS. There was no difference in time to full feeds, length of hospital stay mortality or morbidity.
Keywords: gastroschisis; preformed silo; surgery